2010
DOI: 10.1007/s10144-010-0204-y
|View full text |Cite
|
Sign up to set email alerts
|

The influence of habitat provisioning: use of earthworm burrows by the terrestrial salamander, Plethodon cinereus

Abstract: Studies examining the influence of habitat provisioning by one species on the behavior of other species can provide key insights regarding impacts of ecosystem engineers on the availability of resources to other species. More specifically, an organism's use of additional habitat provided by ecosystem engineers may affect the interpretation of observational or demographic data. We chose to examine the possible influence of earthworms, as ecosystem engineers, on the behavior of terrestrial salamanders, common fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…Cáceres-Charneco and Ransom (2010) proposed that reductions in salamander surface densities could indicate increased underground activity due to the use of burrows created by L. terrestris. Therefore, a decrease in surface density may not represent a true decline in salamander population abundance, but rather a reduction in surface activity due to the loss of suitable surface habitat and the presence of invasive anecic earthworm burrows.…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…Cáceres-Charneco and Ransom (2010) proposed that reductions in salamander surface densities could indicate increased underground activity due to the use of burrows created by L. terrestris. Therefore, a decrease in surface density may not represent a true decline in salamander population abundance, but rather a reduction in surface activity due to the loss of suitable surface habitat and the presence of invasive anecic earthworm burrows.…”
Section: Figmentioning
confidence: 99%
“…Literature regarding the effects of invasive earthworms on salamanders is scarce, but recent investigations into the behavioural interactions between invasive earthworms and the Eastern Red-backed Salamander (Plethodon cinereus (Green, 1818)) have focused on the role of the deep-burrowing, European nightcrawler (Lumbricus terrestris L., 1758) as an ecosystem engineer (Cáceres-Charneco and Ransom 2010;Ransom 2011Ransom , 2012aRansom , 2012b. Ransom (2011Ransom ( , 2012b showed that salamander fossorial activity is influenced by the presence of earthworm burrows and demonstrated potential benefits of invasive earthworm burrows for salamanders, including bolstering overwintering success and serving as refugia from predators.…”
Section: Introductionmentioning
confidence: 99%
“…Invasive earthworms also indirectly affect wildlife by altering habitat structure. Their extensive networks of burrows may benefit some wildlife (Cáceres‐Charneco and Ransom ), but by eliminating leaf litter layers, earthworms may exacerbate soil warming or drying that could negatively affect moisture‐ or temperature‐sensitive taxa (Reich et al . ).…”
Section: Macrocascade Effects Of Earthworm Invasions Of Concern To Somentioning
confidence: 99%
“…Although earthworms can be salamander prey (Maerz et al 2005), if this trophic interaction is the dominant interaction between earthworms and salamanders, one might expect diurnal salamander counts to be positively correlated with earthworm numbers. However, field surveys in Virginia and in New York have indicated that earthworm numbers are negatively correlated with diurnal, above-ground salamander counts (Maerz et al 2009;Cáceres-Charneco and Ransom 2010).…”
Section: Introductionmentioning
confidence: 98%